2011
DOI: 10.1016/j.jval.2011.08.1060
|View full text |Cite
|
Sign up to set email alerts
|

PRM29 Translation and Validation Study of Morisky Medication Adherence Scale (MMAS): The Urdu Version

Abstract: The aim of this paper is to present a compact and coherent within the Bayesian inference method of best meta-analysis model selection as well as to present analytical results in performing Gibbs sampling within the MTC framework. METHODS: In order to perform Gibbs sampling from the posterior distribution in the random effects model of MTC we evaluate the formulas for the conditional distributions for all parameters. We test for the existence of between study heterogeneity and other parametric restrictions by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 0 publications
0
32
3
Order By: Relevance
“…The 12 articles selected included 15 validation processes for six questionnaires that measured adherence to pharmacological antihypertensive treatments ( Table 1 ). The questionnaires were the following: – MGL (two validations) 21 , 27 – Brief Medication Questionnaire (BMQ) (one validation) 27 – Hill-Bone Compliance to High Blood Pressure Therapy Scale (HB Comp Scale) (six validations) 7 , 28 30 – Morisky Medication Adherence Scale (MMAS-8) (three validations) 31 33 – Treatment Adherence Questionnaire for Patients with Hypertension (TAQPH) (one validation) 34 – Martín–Bayarre–Grau (MBG) (two validations). 35 , 36 …”
Section: Resultsmentioning
confidence: 99%
“…The 12 articles selected included 15 validation processes for six questionnaires that measured adherence to pharmacological antihypertensive treatments ( Table 1 ). The questionnaires were the following: – MGL (two validations) 21 , 27 – Brief Medication Questionnaire (BMQ) (one validation) 27 – Hill-Bone Compliance to High Blood Pressure Therapy Scale (HB Comp Scale) (six validations) 7 , 28 30 – Morisky Medication Adherence Scale (MMAS-8) (three validations) 31 33 – Treatment Adherence Questionnaire for Patients with Hypertension (TAQPH) (one validation) 34 – Martín–Bayarre–Grau (MBG) (two validations). 35 , 36 …”
Section: Resultsmentioning
confidence: 99%
“…To assess medication adherence, the Urdu version of the eight-item Morisky Medication Adherence Scale (MMAS-8) was used. [23][24][25] Since Urdu is the national language and is the most widely spoken and understood language in Pakistan, a validated Urdu translation of MMAS-8 26 was used to measure medication adherence. The MMAS-8 score can range between 0 and 8.…”
Section: Data Collectionmentioning
confidence: 99%
“…Thus, the Morisky scale can serve as a screening and monitoring tool to identify those patients with cardiovascular diseases who might have medication adherence problems, but the possibilities of developing interventions aimed at improving adherence on the basis of the results of this scale are limited [46][47][48][49]. This was supported by the observation by Sakthong et al [47], who reported a lack of association of blood glucose concentration with Morisky scale score in diabetic patients.…”
Section: Morisky Medication Adherence Scales (Mmas-4 and Mmas-8)mentioning
confidence: 99%
“…The Morisky Medication Adherence Scale (MMAS) is a short and easy survey identifying barriers to treatment adherence. So far, this is the most extensively studied scale, validated for a large number of diseases [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. The Self-efficacy for Appropriate Medication Use (SEAMS) [50][51], the Hill-Bone Compliance Scale [52][53][54][55], the Brief Medication Questionnaire (BMQ) [56][57][58][59], the Treatment Adherence Questionnaire for Patients with Hypertension (TAQPH) [66], the Martin-Bayarre-Grau questionnaire (MBG) [67][68], and the Adherence Self-Report Questionnaire (ASRQ) [69] focus on patients with chronic cardiovascular diseases, mainly with hypertension.…”
Section: Expert Opinionmentioning
confidence: 99%